Social dynamics in second language accent - Levis, John (John M.); Moyer, Alene, 1961- (Trends in applied linguistics, 2014)
This volume offers a definitive source for understanding social influences in L2 pronunciation, demonstrating the importance of empirical findings from a number of research perspectives, and outlining the directions that future work can take. The aim is to present a coherent argument for the significance of social factors and how they contribute to phonological acquisition.